STRUKTUR PEREKONOMIAN INDONESIA DAN PENGARUHNYA PADA INDUSTRI KAYU MENTAH - Socia Prihawantoro, Budy P. Resosudarmo (UGM, 1999)
It is commonly known, in Indonesia that a high growth rate of log production induces a high rate of deforestation. Hance, to reduce the rate of deforestation, it is necessary for Indonesia to decrease its log production.